Romantisme Cerpen “Hujan untuk Ayu” Karya Heri Isnaini dengan Pendekatan Struktural - Neng Alismi Anjarwati (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Literature serves as a medium that can be used to educate and entertain its audience. In comprehending a literary work, readers can employ various approaches, one of which is the structural approach. This approach can be utilized to analyze a short story. This study aims to analyze a short story titled "Hujan untuk Ayu" by Heri Isnaini through a structural approach. The research was conducted by collecting data through qualitative methods and analyzing the elements that constitute the short story. The data used is the short story "Hujan untuk Ayu" by Heri Isnaini, which was published in the daily newspaper Pos Jawa Radar Banyuwangi on July 20, 2024. By conducting a study using a structural approach, readers can more easily understand the overall meaning contained in the short story. The research results will describe the elements that make up the short story, such as (1) theme, (2) plot, (3) characters and characterization, (4) setting, (5) message, (6) point of view, and (7) style of language found in the short story "Hujan untuk Ayu" by Heri Isnaini. It is hoped that this research can provide an understanding of analyzing a short story using a structural approach.